Comparative Study of Split Air Conditioner Performance on Pipe Length Variations in R32, R410A, and R290 Refrigerants - Imam Nursyahied; Thaha Ismail Jayadinata; Alynda Natasya Putri Ardianto; Aris Sunawar; Readysal Monantun (Universitas Negeri Jakarta, 2026)
Split air conditioners are one of the most commonly used air conditioning systems due to their compact design and flexible installation. The system consists of two units connected by copper pipes as a refrigerant circulation line. This study presents a comparative analysis of the thermodynamic performance of split AC on pipe length variations using three refrigerants, R32, R410A, and R290, with a simulation approach based on CoolProp v6.4 and REFPROP v10.0 software. The length variations of the tested pipes are 15, 20, 25, and 30 m with operating conditions according to ISO 5151:2017 standards. The parameters evaluated included cooling capacity (Qe), input power (Pinput), energy efficiency ratio (EER), and pressure drop (Δp). The accuracy of both software is measured using MAPE and RMSE metrics against manual calculations as a reference. The simulation results showed that the increase in pipe length led to an average decrease in Qe of 10.3-10.4% from the 15 m to 30 m pipe length in all three refrigerants. R290 recorded the highest EER (3.87-3.48), followed by R32 (3.72-3.33), and R410A (3.36-3.01). R410A produces the largest pressure drop (25.87 kPa at 30 m), while R290 has the lowest pressure drop (12.56 kPa). Accuracy analysis showed that REFPROP was more accurate than CoolProp on all parameters with an average MAPE difference of 0.57%, although the difference between the two was relatively small. Large deviations in the Δp parameter (>168%) are due to fundamental flow model differences, not thermodynamic errors. The results of this study provide a scientific reference in the selection of the optimal refrigerant and simulation software for split air conditioning installations with varying pipe lengths.